2021
DOI: 10.1111/jsap.13374
|View full text |Cite
|
Sign up to set email alerts
|

CTfindings, management and short‐term outcome of dogs with pyothorax: 101 cases (2010 – 2019)

Abstract: To describe diagnosis, CT findings, management and short-term outcome of a large population of canine pyothorax cases.MethOds: Retrospective analysis of 101 canine pyothorax cases at two UK referral centres. Medical records and CT images were reviewed. Dogs were included if pre-and post-contrast CT was performed within 48 hours of presentation.Results: CT abnormalities included pleural thickening (84.1%), pannus (67.3%), pneumothorax (61.4%), mediastinal effusion (28.7%), pulmonary (13.8%) and mediastinal (7.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
1
2
2
Order By: Relevance
“…In another study of pyothorax, 75% of cats came from multi‐cat households, but those cats did not have a history of fighting or bite wounds and the authors could only determine an etiology for pyothorax in 3/55 cases 11 . Most cats with pyothorax in our study had access to the outdoors (59%), similar to findings in large studies of pyothorax from Europe 3,11 . Several studies have failed to discover an underlying cause for pyothorax in cats, 1,11 whereas only 2/29 cats did not have a cause of pyothorax identified in our study.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…In another study of pyothorax, 75% of cats came from multi‐cat households, but those cats did not have a history of fighting or bite wounds and the authors could only determine an etiology for pyothorax in 3/55 cases 11 . Most cats with pyothorax in our study had access to the outdoors (59%), similar to findings in large studies of pyothorax from Europe 3,11 . Several studies have failed to discover an underlying cause for pyothorax in cats, 1,11 whereas only 2/29 cats did not have a cause of pyothorax identified in our study.…”
Section: Discussionsupporting
confidence: 77%
“…Some studies have reported monomicrobial infection in the majority of both cat 4 and dog 3 cases of pyothorax; however, the majority of cases here and in other studies 2 , 10 , 18 had polymicrobial infection, which emphasizes the need to perform both aerobic and anaerobic cultures. Antimicrobial susceptibility testing is essential to ensure efficacy of treatment against all infecting organisms.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations